Investigation on microbial contamination of cereal-based complementary foods for infants and young children in Henan in 2018 - Dacheng GUO; Huixia CHUI; Haoyu QI; Xiuli ZHANG; Hua REN; Fengli LI; Zeyu WANG (Zhongguo shipin weisheng zazhi, 2020)
Objective To understand the hygienic status of cereal-based complementary foods (CBCFs) for infants and young children (IYC) in Henan Province and therefore provide basic data for food safety risk assessment and standard formulation. Methods Sampling and testing were performed according to the method provided in the work manual of 2018 national food pollutants and hazardous factors risk monitoring.103 samples of CBCF for IYC were collected in Henan Province, and then the contamination of Enterobacteriaceae, Bacillus cereus, Listeria monocytogenes and Cronobacter were detected, respectively. Matrix-assisted laser desorption ionization-time-of-flight mass spectrometry was used to identify the suspicious colonies. Results The detection rates of Enterobacteriaceae and Cronobacter in 103 samples were 0.97% (1/103) and 5.83% (6/103), respectively. They were all detected in ready-to-eat CBCFs for IYC from convenience stores/retail stores, mainly produced in Jiangxi and Fujian Provinces. Five of the six Cronobacter positive samples were labeled before the initial stage of supplementary food addition. The quantitative result of Bacillus cereus in the range of 10-103 CFU/g were obtained in 9 samples, with a detection rate of 8.74% (9/103), which were produced from Guangdong, Jiangxi, Fujian, Heilongjiang and Sichuan Provinces. The sampling sites were supermarkets and convenience stores/retail stores, of which 8 were ready-to-eat CBCFs for IYC. Conclusion The CBCFs for IYC sold in Henan Province, especially the ready-to-eat CBCFs for IYC, were contaminated by Cronobacter and Bacillus cereus. Most of these positive products targeted the population at the beginning of the supplementary foods, which might result in greater food safety risks. It was suggested that the microbial requirements of Cronobacter and Bacillus cereus should be added to the ready-to-eat CBCFs for IYC, which could reduce the potential food safety problems.